International Symposium on Islam and Modernity: 19-21 Jumada al Awwal 1413/ 4-6 November 1993 Karachi, Pakistan (American Journal of Islam and Society, 1994)
The three-day seminar on “Islam and Modernity” was held under thejoint auspices of the Goethe Institute (Karachi), the International Instituteof Islamic Thought (Islamabad), and the Islamic Research Institute (Islamabad).Thirty scholars from Pakistan and four scholars from Germanyparticipated as delegates, and an equal number of other scholars,journalists, and bureaucrats attended as observers. The seminar addressedfour themes: a) The State: Legitimation and Participation; (b) The Law:Law and Justice; (c) The Economy and Finance: Economy and Ethics;and (d) Society: Equality and Justice. The sesions were arranged to giveadequate time to the presenters and for follow-up discussion.In general, the seminar sought to create a better understanding andappreciation of the current self-assertion in the Muslim world and theways in which Muslims are dealing with modernity. There is a growingbelief among Muslims that it is possible to achieve developmental goals,as well as those of material and social welfare, within the framework ofIslam. This, it is believed, would save their societies from moral degradation,the breakdown of social and family structures, the dehumanizationof human life, and other negative features of western modernity.This resurgence often generates fear and apprehension in the West,a reaction that might be partially due to sporadic acts of violence by Muslimextremists. The West’s perception of Islamic resurgence is thuscolored, which undermines its ability to see it for what it really is. Despitethis, however, many people in the West feel the need for a betterunderstanding of the changes taking place in Muslim societies and forentering into a dialogue with their Muslim counterparts in order toexplore the possibility of promoting mutual respect and creating anatmosphere of meaningful and peaceful coexistence.In addition to the general divide between Islam and the West, thereis a secular vs. Islamist divide within Muslim societies. Some adhere tothe secular view of life and seek to confine religion to a private concern,while others want to restructure the individual and all elements of sociallife according to Islamic principles and values ...